Identification of the development mechanisms of an explosive cyclone in the central Mediterranean with the aid of the MSG satellite images - Kouroutzoglou, J.a b; Flocas, H.A.a; Hatzaki, M.a; Keay, K.c d; Simmonds, I.d; Mavroudis, A.e (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
The development mechanisms of an explosive cyclone over Central Mediterranean are examined, by relating the cloud patterns in the infrared, water vapour and visible channels of the Meteosat Second Generation (MSG) satellite images, to the surface-upper air operational analyses and thermodynamic parameters, including potential and geostrophic vorticity analyses, potential and equivalent potential temperature, static stability and thermal heat fluxes. The specific case study derived from an updated climatology of Mediterranean explosive cyclones for the 2002-2010 period, being performed with the aid of the University of Melbourne Cyclone Tracking scheme (MS algorithm) and ERA-INTERIM datasets. It was found that during the ordinary cyclogenesis the increased mid-upper level relative humidity over Northern Algeria along with the enhanced moisture gradient in the area between Portugal and Spain; indicate the existence of a jet -streak, with the dry zone to be located on the cold side of the jet axis. The descent of the dry air is more pronounced within the left exit region of the jet streak in the poleward portion of an upper confluence zone. Six hours later, the eastward movement of the cloud pattern in the Northern African coasts significantly resembles the structure of a baroclinic leaf, being related to the early stages of surface frontogenesis, due to the deformation process within a strong wind field. During the time of rapid deepening, when the surface cyclone propagated from the Northern African coasts towards the area of Sicily - Gulf of Taranto, the development is characterised by the transition from the baroclinic leaf structure to the comma cloud one and finally the formation of a bent-back occlusion. © 2013 SPIE.
Keywords: Algorithms; Development mechanisms; Era interims; Explosives; Geostrophic vorticity; Infrared radiation; Meteosat second generations; MSG satellites; remote sensing; Satellites; Storms; Thermodynamic parameter; University of Melbourne; Water vapor; Water vapour